Increasing Students' Awareness of Cultural Diversity through Symbolic Modeling Techniques Based on the Art of Syair Gulung - Halida Halida; Yogi Damai Syaputra; Monalisa Monalisa; Syawaluddin Syawaluddin; Randi Saputra; Elvina Gusman (Journal of Innovation in Educational and Cultural Research, 2024)
Indonesia has cultural diversity, but currently, it is found that many students still need to gain more awareness of cultural diversity. This will have an impact on the ineffectiveness of daily life. This research aims to determine the application of symbolic modeling techniques containing syair gulung to increase students' awareness of cultural diversity. The art of syair gulung has many moral messages, including the value of unity, respect for differences, care, and tolerance. The research design used pure experimentation with a one-group pretest-posttest model. The research subjects were junior high school students in Pontianak City, with an age range of 12 years to 14 years. The instrument used is the cultural diversity awareness scale. Data were analyzed through parametric statistics with hypothesis testing using the paired sample t-test to compare treatment results. The research results show that symbolic modelling techniques based on the art of syair gulung can increase students' awareness of cultural diversity. The results of this research enrich the scientific knowledge of multicultural counselling for counsellors in schools. This research recommends that it can be applied to other psychological aspects and collaborate with the culture in Indonesia. The research results recommend that guidance and counseling teachers apply the results of this research in their schools. Further researchers are advised to conduct research using symbolic modeling techniques with local culture in Indonesia.